Predicting peatland carbon fluxes from non‐destructive plant traits. (22nd May 2017) - Goud, Ellie M.; Moore, Tim R.; Roulet, Nigel T.
Summary: Determining the plant traits that best predict carbon (C) storage is increasingly important as global change drivers will affect plant species composition and ecosystem C cycling. Despite the critical role of peatlands in the global C cycle, trait–flux relationships in peatlands are relatively unknown. We assessed the ability of four non‐destructive plant traits to predict carbon dioxide (CO2 ) and methane (CH4 ) fluxes over two growing seasons in a temperate peatland in Ontario, Canada. We examined relationships between C‐fluxes and leaf area, leaf persistence (deciduous, evergreen), growth form (woody, herbaceous) and aerenchyma tissue. To explore potential inconsistencies between different scales of data aggregation, traits were analysed at the level of plots, species and microsites. CO2 fluxes showed a positive relationship with leaf area and leaf persistence, and a negative relationship with proportion of woody species. CH4 fluxes showed a positive relationship with aerenchyma and leaf area. The significance of trait–flux relationships differed based on whether data were averaged at the level of plot, species or microsite. We recommend applying leaf area as a non‐destructive trait to other systems where it is not ideal to measure traits destructively. A better understanding of the relationships between above and below‐ground traits is likely needed to further explain variation in ecosystem respiration and CH4 fluxes from plant traits. A lay summary is available for this article. Abstract : Lay Summary